Job stressors and smoking cessation among Malaysian male employees - Yasin, Siti Munira; Retneswari, Masilamani; Moy, Foong Ming; Darus, A.; Koh, David (2012)
Job stressors may reduce the likelihood of quitting smoking. To assess the association between job strain, smoking behaviour and smoking cessation among Malaysian male employees involved in a smoking cessation programme. The study was conducted among employees in two major public universities in Malaysia. All staff from both universities received an invitation to participate in this study. At the start of treatment, participants completed a questionnaire on sociodemographic variables, smoking habits and the Malay version of the Job Content Questionnaire (JCQ). The JCQ consists of scales of job control, job demand, supervisor support, co-worker support, job insecurity, job decision latitude and job skill discretion. Behaviour therapy with free nicotine replacement therapy (NRT) was given as treatment for two months. Participants were contacted at 1 week, 3 months and 6 months to determine their smoking status. One hundred and eighty five staff from both universities responded and voluntarily showed interest in quitting. At three months (OR = 8.96; 95 CI: 1.14-70.76) and six months (OR = 8.9; 95 CI: 1.15-68.65), men with higher co-workers' support demonstrated a higher likelihood of quitting. Smokers in a 'passive job' also demonstrated higher likelihood of quitting compared with those working in the 'low strain' category at six months (OR = 9.92; 95 CI: 1.20-82.68). No meaningful associations were found between other psychosocial job variables and smoking cessation. A positive relationship with and support from co-workers are important factors for workplace smoking cessation.